The Dynamics of The Sekura Tradition in West Lampung from the Perspective of Van Peursen's Cultural Philosophy - Winda Pitriani Parhamah; Aman Aman; Wildan Ichzha Maulana; Roro Wilis (Universitas Pendidikan Ganesha, 2026)
Discussing local traditions in an area is inseparable from the influence of the times, culture, and dynamic social conditions of its supporting communities, thus opening up opportunities for the process of deconstruction, including the reinterpretation of a tradition as conceptualized by Van Peursen. This research aims to identify, critically analyse, and describe the dynamics of the development of the Sekura tradition in West Lampung based on the conceptualisation of Van Peursen's cultural philosophy, including mystical, ontological, and functional stages. This research employs a qualitative approach, utilizing a literature study method to obtain primary data from books published by the Ministry of Education and Culture, as well as books on Sekura Traditions in Coastal Lampung Communities. Secondary data sources were obtained from journals, local government publications, and research documents from various institutions. The analysis was carried out using Klaus Krippendorff's content analysis model and strengthening credibility through triangulation of sources. The results of the study show that the Sekura tradition at the mystical stage functions as a grounded Islamic spiritualism, at the ontological stage becomes a space of social cohesion and a symbol of collective identity, and then at the functional stage transforms into a tourism commodity that strengthens the local economy.